Aktivitas Tepung Tempe Terhadap Kadar Kolesterol Total Tikus Model Hiperkolesterolemia - Agustin, Firda; Arinda, Ayu Dwi; Febrianti, Zanelia Sekar Ayu; Rizky, Ika Karunia; Andriani, Mitha (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Hypercholesterolemia is a condition characterized by total cholesterol levels in the body exceeding normal ranges. Tempeh flour has a longer shelf life and higher bioactive compound content compared to traditional tempeh. This study aimed to evaluate the effect of tempeh flour on total cholesterol levels in a hypercholesterolemic Wistar rat model. The study utilized male Wistar rats weighing 120–200 grams, with a total of 16 rats divided into three groups: negative control (K-) given standard rat feed (30 g/rat/day) and ad libitum water; positive control (K+) fed a high-fat diet (2 ml/200 g body weight via gastric gavage) and ad libitum PTU solution (100 ml); and treatment group (P), consisting of hypercholesterolemic rats given tempeh flour (1.8 g/200 g body weight via gastric gavage). Total cholesterol levels were measured using the CHOD-PAP method. Data were analyzed using One-Way ANOVA and paired t-tests. The initial (T0) data analysis showed no differences in total cholesterol levels between groups. Pretest and posttest total cholesterol levels revealed no significant differences in the K- group (p=0.072) or K+ group (p=0.056), while the P group demonstrated a significant difference (p=0.002). The mean total cholesterol levels in the K- group decreased from 71.17 ± 6.853 (pretest) to 65.17 ± 6.616 (posttest). In the K+ group, the levels decreased from 148.80 ± 11.122 (pretest) to 122.60 ± 20.144 (posttest). In the P group, the mean total cholesterol levels significantly declined from 127.40 ± 32.508 (pretest) to 79.20 ± 23.594 (posttest). In conclusion, tempeh flour effectively reduces total cholesterol levels in hypercholesterolemic Wistar rats.